Efecto de la orientación de las flores sobre los caracteres reproductivos de Myrtillocactus geometrizans - Aguilar García, Sandra Aracely (Universidad Autónoma Metropolitana, 2015)
In Cactaceae, the interception of photosynthetic active radiation (PAR) differs among opposite sides of the stem, determining the availability of resources for reproduction, since it has been suggested that there is no translocation of resources between ribs. It has been shown that the production of reproductive structures in columnar cacti distributed in the northern hemisphere is higher in the south side of the stem where the interception of RFA is higher. Myrtillocactus geometrizans (Mart.) Console is an arborescent columnar cactus, whose flowers and fruits show a preferential orientation to the south. This research project deals with the effect of the orientation of flower buds on reproductive traits in this species and aimed to compare in flower buds with contrasting orientations (north vs. south) male and female characters and the reproductive system. This was done with flower buds and flowers that were collected at a site in Zapotitlán Salinas Puebla. It was determined the number and size of reproductive structures (i.e. number and sizes of anthers per flower, number, diameter and pollen viability, size and number of ovules from the ovary), and reproductive system by pollen ratio was determined P/O). In addition in vitro pollen germination to determine the percentage of germination and pollen tube length was tested. The results show a significant effect in seven male and two female floral features out of 10 and four measured traits, respectively, as well as the P/O. It is, oriented southeast stem buds have significantly increased production of anthers, more pollen grains per anther and per flower bud. Pollen grains have a larger average diameter, greater percentage of viability and germination and longer pollen tube. The length and area of the ovary and P/O ration is higher in flower buds oriented southeast. According to the classification of Cruden, M. geometrizans has a facultative xenogamy reproductive system. This study raises the need for more detailed studies of the variation in the reproductive system between contrasting orientations. The results show that the availability of resources on opposite sides of stem have positive influence both in male floral traits as in female reproductive structures, which may also have an effect on reproductive success of flowers with different orientations of M. geometrizans.; En cactáceas, la intercepción de radiación fotosintéticamente activa (RFA) difiere entre lados del tallo son diferente orientación, determinando la disponibilidad de recursos para la reproducción, ya que se ha sugerido que no hay translocación de recursos entre costillas. Algunos estudios han demostrado que la producción de estructuras reproductivas en cactáceas columnares distribuidas en el hemisferio norte, es mayor en la cara sur del tallo donde la intercepción de RFA es mayor. Myrtillocactus geometrizans (Mart.) Console es un cactus columnar arborescente, cuyas flores y frutos muestran una orientación preferencial hacia el sur. El presente proyecto de investigación aborda el efecto de la orientación de los botones florales sobre los caracteres reproductivos en esta especie y tuvo como objetivos comparar en botones florales con orientaciones contrastantes (norte vs. Sur) caracteres masculinos y femeninos y el sistema reproductivo. Esto se realizó con botones florales y flores que fueron colectados en un sitio de Zapotitlán Salinas Puebla. Se determinó el número y tamaño de estructuras reproductivas (i.e. número y tamaños de las anteras por flor, número, diámetro y viabilidad del polen, número de óvulos y tamaño del ovario), y el sistema reproductivo mediante la relación polen:óvulo (P/O). Además de realizar pruebas de germinación in vitro de polen para evaluar el porcentaje de germinación y la longitud del tubo polínico. Los resultados muestran un efecto significativo en siete caracteres florales masculinos y dos femeninos de los diez y cuatro que fueron medidos respectivamente, así como en la relación P/O. Los botones orientados hacia el sureste del tallo tienen, significativamente una mayor producción de anteras, más granos de polen por antera y por botón floral. Los granos de polen tienen mayor diámetro promedio, y mayor proporción de viabilidad y de germinación, así como mayor longitud del tubo polínico. La longitud y área del ovario y la relación P/O es mayor en los botones florales orientados al sureste. De acuerdo con la clasificación de Cruden, M. geometrizans tiene un sistema reproductivo xenógamo facultativo. Este estudio plantea la necesidad de realizar estudios más detallados sobre la variación en el sistema reproductivo entre orientaciones contrastantes. Los resultados muestran que la disponibilidad de recursos en lados opuestos del tallo influyen positivamente, tanto en los rasgos florales masculinos como en los femeninos de las estructuras reproductivas, por lo que también puede tener un efecto sobre el éxito reproductivo de flores con diferentes orientaciones de M. geometrizans.